P142 Evaluation of quantitative phase imaging for automated assessment of histopathological remission in patients with Ulcerative Colitis. (30th January 2023) - Bokemeyer, A; Buskermolen, J; Ketelhut, S; Tepasse, P; Vollenberg, R; Vieth, M; Kemper, B; Bettenworth, D
Abstract: Background: Ulcerative colitis (UC) is characterized by chronic intestinal inflammation. Histological remission has become an efficacy outcome in clinical trials and might have the potential to modify the course of UC. Quantitative phase imaging including digital holographic microscopy (DHM) can be used for objective and automated evaluation of tissue morphology and density. Our study aimed to evaluate DHM for quantifying histological inflammation in UC patients. Methods: In a monocentric prospective study, UC patients undergoing colonoscopy were included. Disease activity was measured by the total Mayo Score. DHM was used to determine the refractive index (RI) in mucosal biopsy samples obtained during colonoscopy. RI values were correlated with histological disease activity as assessed by the Nancy histological index [NHI]. Results: In total, mucosal biopsy samples from 21 UC patients were included to the analysis. On average, UC patients had a moderate disease activity as reflected by a partial Mayo score of 3.1 (SEM ± 0.6), an endoscopic Mayo subscore of 1 (SEM ± 0.2) and a total Mayo score of 4.1 (SEM ± 0.8). The mean NHI was 1.3 (SEM ± 0.2) and the mean RI was 1.349 (SEM ± 0.0003). RI values as determined by DHM correlated strongly with the histological disease activity as determined the NHI (p<0, 001 and R 2 =0.282). Similarly, a marked correlation was found using alternative histopathological indices (Geboes score, Riley index, Robarts histopathological index; all p<0.001). Conclusion: Our data demonstrate that DHM is appropriate to assess intestinal inflammation in UC patients and that it may be an alternative or supplemental tool to conventional histopathological assessment.